Enhanced Signaling Through the TLR9 Pathway Is Associated With Resistance to HIV-1 Infection in Chinese HIV-1–Exposed Seronegative Individuals - Jiang, Junjun; Hu, Xi; Li, Wenwei; Liu, Jie; Liang, Bingyu; Chen, Hui; Huang, Jiegang; Zang, Ning; Ning, Chuanyi; Liao, Yanyan; Chen, Rongfeng; Lai, Jingzhen; et al. (Frontiers in Immunology, 2020)
Innate immunity is the first line of defense against invading pathogens and may mediate HIV-1 resistance in HIV-1–exposed seronegative (HESN) individuals. This study aims to identify components of innate immunity that confer natural HIV-1 resistance in Chinese HESN individuals. Specifically, we compared the expression levels of Toll-like receptors (TLRs) and associated pathway molecules in peripheral blood mononuclear cells (PBMCs), monocytes/macrophages, and plasma obtained from HESN and control individuals. HESN individuals had higher expression of TLR9, IRF7, IFN-α/β, RANTES, and MIP-1α/1β in PBMCs and plasma than control subjects. Upon TLR9 stimulation, significantly higher expression of TLR9 and IRF7, as well as higher production of IFN-α/β, RANTES, and MIP-1α/1β, was observed in PBMCs and monocytes/macrophages from HESN individuals than in the corresponding cells from control individuals. More importantly, both with and without TLR9 stimulation, the levels of HIV-1 replication in monocyte-derived macrophages (MDMs) from HESN individuals were significantly lower than those in MDMs from control individuals. These data suggest that increased TLR9 activity and subsequent release of antiviral factors contribute to protection against HIV-1 in HESN individuals.